The value and broader impacts of agricultural and environmental scientific meetings - Aaron Lee M. Daigh; Samira H. Daroub; Peter M. Kyveryga; Mark E. Sorrells; James A. Ippolito; Endy Kailer; Shannon L. Osborne; Felix B. Fritschi; Wade E. Thomason; Ronald F. Turco; Michael A. Grusak; Carrie A. M. Laboski; et al. (Agricultural & Environmental Letters)
Abstract The socioeconomic value of content presented at the ASA‐CSSA‐SSSA (where ASA‐CSSA‐SSSA is American Society of Agronomy–Crop Science Society of America–Soil Science Society of America) Annual Meetings from 2014 to 2023 is estimated at $64.2 billion and is presented in this commentary as a thought exercise, highlighting the potential scale of research dissemination in scientific meetings. Scientific meetings are instrumental for propelling the quality and advancement of research via fostering timely feedback, knowledge dissemination, fresh perspectives, stimulation for networking and new collaborations, preparing scientists for public engagement, and addressing contemporary challenges of cultural accessibility and opportunity. Additionally, the broader impacts include near‐term benefits to agricultural and environmental scientists that can transform careers and perspectives on the world, especially for students and early career members. The benefits from these impacts on scientists are then anticipated to propagate into broader and longer term positive impacts on humanity worldwide. In this commentary, we offer the above as a provocation to spark peer discussion on evaluating scientific meetings’ contributions, alongside a working list of broader impacts to inspire philosophical and methodological innovations for quantifying their value.